Optimizing the performance of cattle fattening to rescue drought-hit farmers in Senegal - Sow, Fafa; Worou, Nadine; Faye, Aliou; Houessionon, Prosper; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) helps deliver a climate smart African future driven by science and innovation in agriculture. The initiative works to make climate information services and climate smart agriculture more accessible to millions of smallholder farmers across Africa. With better access to technology and advisory services, farmers can better anticipate climate-related events to take preventative action that helps their communities safeguard livelihoods and the environment. AICCRA has teams in six countries: Senegal, Ghana, Mali, Ethiopia, Kenya and Zambia, who work in four key areas – knowledge, partnerships, innovation and gender and social inclusion.